Development of Virtual Hologram Audio Visualizer Box Technology to Improve Physical Fitness - Arief Darmawan; Tatok Sugiarto; Surya Adi Saputra; Ahadi Priyohutomo; Amirina Surya Mahardikarani (Indonesian Journal of Physical Education and Sport Science)
Study purpose. Develop virtual hologram box technology in improving the physical fitness of junior high school students